A comparative study on surface strengthening characterisation and residual stresses of dental alloys using laser shock peening. Issue 15 (18th November 2021) - Gurusami, K.; Shanmuga Sundaram, K.; Chandramohan, D.; Dinesh Kumar, S.; Vasantha Srinivasan, P.; Sathish, T.
ABSTRACT: In this work, Ni–Cr and Co–Cr alloys at untreated and treated conditions by laser are studied. Optical and scanning electron microscope, an X-ray diffractometer with an energy dispersive X-ray spectrometer, micro-hardness and digital surface roughness measuring testers are used to analyse the characterisation of both the unirradiated and irradiated specimens. The high surface micro-hardness is formed in the laser irradiated region of the sample during laser shock peening (LSP). In this case, high dislocation densities can produce. The LSP method involves with recoil pressure loading at the sample surface with minimum heating effects in the laser treated region. Hence in this work, the LSP of Ni–Cr and Co–Cr alloys is investigated to understand the influence of a power density, pulse density, pulse duration and irradiated laser spot diameter on the treated layer characteristics. The micro-hardness data is compared using ANOVA and post-hoc Tukey test. It is observed that the selected laser parameters have significant influence on the resulting surface characteristics. The experimental results of LSP with the WCM process show the microstructure considerably refined grains via arrays of dislocation and thereby impart a favourable compressive residual stress filed for improving mechanical properties and mastication strength.